Implementation of the 2023 Criminal Code (KUHP) and the 2025 Criminal Procedure Code (KUHP) in Criminal Justice Practices: An Analysis of Judicial Policy on Supreme Court Circular Letter Number 1 of 2026 - Deddy Isniyanto (Eduvest - Journal of Universal Studies, 2026)
The enactment of the 2023 Indonesian Criminal Code (KUHP 2023) and the 2025 Criminal Procedure Code (KUHAP 2025) marks a fundamental paradigm shift in Indonesia’s criminal justice system. These reforms require a consistent application of law to prevent fragmented judicial practices and sentencing disparities. In this context, the Supreme Court issued Supreme Court Circular Letter Number 1 of 2026 as a guideline for the implementation of the new Criminal Code and Criminal Procedure Code. This article aims to analyze the position and function of Supreme Court Circular Letter Number 1 of 2026 as a form of judicial policy, as well as its implications for judicial independence and court governance. This study employs a normative juridical method using statutory, conceptual, and judicial policy approaches. The findings indicate that Supreme Court Circular Letter Number 1 of 2026 constitutes a strategic and transitional judicial policy instrument to maintain the unity of criminal justice practices. Nevertheless, its implementation must be positioned proportionately as an interpretative guideline to prevent it from evolving into a form of quasi-legislation that may unduly restrict judicial discretion. Accordingly, future judicial policy of the Supreme Court should be strengthened through an adaptive, reflective, and continuously evaluated approach.